Education and equality of opportunity in Trinidad and Tobago - Baksh, Ishmael J.
This article addresses the issue of equality of opportunity in Trinidad and Tobago. It examines: 1) the social background of students attending two types of secondary schools, and 2) differences between the two types of secondary schools regarding students' self-concepts, attitudes toward technical and academic forms of education, and educational and occupational expectations. The results of the investigation suggest that, despite government and the society's expectations, education is likely to function as a means of restricting or controlling social mobility from the lower classes; that true equality does not exist since students from lower-class backgrounds are assigned in disproportionately large numbers to junior secondary (as compared with grammar) schools, where they are more likely to be oriented towards a technical or vocational type of education and towards lower educational and occupational goals
Republished in "Caribbean Sociology: Introductory Reading" (pp. 712-725), edited by Christine Barrow and Rhoda Reddock. Kingston, Jamaica: Ian Randle, 2001
Keywords: Equal education